Causes of Anemia in Patients Seen in a Rural Community Hematology Clinic - Featherstone, Sarah; Cathcart-Rake, William; Zackula, Rosey; Beck, Larry (Kansas Journal of Medicine, 2022)
Introduction. Anemia is a common medical disorder seen in consultation by hematologists. This study was performed to determine the incidence of the etiologies causing anemia in patients referred to the hematologists at Tammy Walker Cancer Center (TWCC) in the rural Kansas community of Salina. An additional goal of the study was to compare the frequencies of different etiologies for anemia in this cohort of patients with those previously reported by four academic medical centers. Methods. A retrospective review of the medical records of 152 patients seen at TWCC between August 2015 and May 2019 was performed. The patient’s history and physical exam, complete blood count and various additional hematologic studies ordered at the discretion of the TWCC hematologist were used to determine the etiology of each patient’s anemia. Results. The most common causes of anemia found in the chart review were iron deficiency (48.7%), hematologic malignancy (14.5%), chronic inflammation (13.8%), renal insufficiency (11.2%), and unexplained anemia (9.9%). While the incidences of anemia due to hematologic malignancy, chronic inflammation, and renal insufficiency were similar to that reported previously by four academic medical centers, significantly more iron deficiency and less unexplained anemia were found in the patients referred to TWCC. Conclusions. The causes of anemia in patients seen at TWCC were similar to those reported by academic medical centers; however, the incidences were different. The differences in findings may reflect dissimilarities in the demographics of referral populations, the duration and extent of the evaluation at TWCC, or referral patterns.